The Mkapa Years collected speeches:challenges and policy responses (Dar es Salaam Mkuki na Nyota, 2013)
This collection of speeches, in three volumes, by the President of the United Republic of Tanzania's Third Phase Government, Benjamin William Mkapa (1995-2000), will serve primarily as reference documents to the vision of what he attempted to achieve in his ten years of leadership. His tenure as a leader came at a time when Tanzania's economy was in dire condition. The legacy of the command economy, which had been in place for much of 1970s and 1980s, was still felt. There was resistance to change to adopt a market economy, evident in the political tensions and debates about privatisation, an approach following Structural Adjustment Programmes, imposed by IMF and the World Bank, that had led to stagnation of the economy; high inflation, deteriorating health, education, communication and transport sector services; and general gloom in the country especially among the poor.
Includes bibliographies
Keywords: Economy